Comparison of the Effectiveness of Positive Thinking Training and Emotional Self-Regulation Training on Self-Compassion and Psychological Well-Being in Mothers of Children with Autism Spectrum Disorder - Zaghian , Mahshid; Sharifi, Tayebeh; Ghasemi Pirbalouti , Mohammad (KMAN Counseling & Psychology Nexus, 2026)
The present study was conducted with the aim of comparing the effectiveness of positive thinking training and emotional self-regulation training on self-compassion and psychological well-being in mothers of children with Autism Spectrum Disorder (ASD). This study was a quasi-experimental design with a pretest–posttest control group and a two-month follow-up. The statistical population consisted of mothers of children with ASD in the city of Isfahan during the years 2024–2025. From this population, 60 mothers were selected through purposive sampling and were then randomly assigned to two experimental groups and one control group. The research instruments included the Self-Compassion Scale (Neff, 2003) and the Psychological Well-Being Questionnaire (Ryff, 2002). Both experimental groups received interventions consisting of eight 90-minute sessions of positive thinking training and emotional self-regulation training. Data were analyzed using repeated measures analysis of variance (ANOVA) and Bonferroni post hoc tests. The results indicated that positive thinking training and emotional self-regulation training had a significant effect on parenting stress and distress tolerance (p < 0.001). The effects of both interventions were maintained at the two-month follow-up stage. Furthermore, emotional self-regulation training demonstrated greater effectiveness compared to positive thinking training in improving self-compassion and psychological well-being (p < 0.001). The findings suggest that therapists should prioritize emotional self-regulation training over positive thinking training to enhance self-compassion and psychological well-being in mothers of children with ASD.